2017
DOI: 10.1007/s00464-017-6013-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing discharge disposition after colectomy

Abstract: The majority of perioperative factors associated with extended care after colectomy are patient driven. The adoption of oral antibiotics as bowel preparation, minimally invasive surgery, and accelerated recovery protocols may reduce post-acute care placement after elective colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…This study used NSQIP in a similar manner to determine if operative approach, in addition to other variables, influenced the discharge destination for patients undergoing rectal prolapse surgery. The nomogram in Figure 1 displays risk factors for requiring postoperative PAC that are consistent with risk factors seen in other studies, including advanced age, MIS, comorbidities and postoperative complications [18,20–23].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This study used NSQIP in a similar manner to determine if operative approach, in addition to other variables, influenced the discharge destination for patients undergoing rectal prolapse surgery. The nomogram in Figure 1 displays risk factors for requiring postoperative PAC that are consistent with risk factors seen in other studies, including advanced age, MIS, comorbidities and postoperative complications [18,20–23].…”
Section: Discussionsupporting
confidence: 71%
“…This study used NSQIP in a similar manner to determine if operative approach, in addition to other variables, influenced the discharge destination for patients undergoing rectal prolapse surgery. The nomogram in Figure 1 displays risk factors for requiring postoperative PAC that are consistent with risk factors seen in other studies, including advanced age, MIS, comorbidities and postoperative complications[18,[20][21][22][23].The cost of PAC after surgery varies by hospital system. One study reported a cost of USD 3345-6104 after colectomy, with the strongest Nomogram for prediction of morbidity: the nomogram demonstrates the likelihood of postoperative morbidity based on total points accumulated based on surgical approach (MIS, minimally invasive), functional status, American Society of Anesthesiologists (ASA) classification, body mass index (BMI) and smoking (c-statistic 0.614)…”
supporting
confidence: 63%
See 2 more Smart Citations
“…While evidence support the utility of ERAS to accelerate surgical patients discharge from hospital to home, the benefit of such programmes to avoid hospital readmission remains to be demonstrated (Greco et al., 2014; Lv et al., 2012; Varadhan et al., 2010; Zhuang et al., 2013). In fact, several studies have reported high readmission rates (from 9%–25%) in the 30 days following elective colorectal surgery (Adamina et al., 2011; Al‐Mazrou et al., 2018; Damle & Alavi, 2016; Lawson et al, 2014). These statistics suggest some difficulties in colorectal patients’ transition from hospital to home.…”
Section: Introductionmentioning
confidence: 99%